2018
DOI: 10.7150/jca.26794
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CK19 mRNA Using One-step Nucleic Acid Amplification (OSNA) in Prostate Cancer: Preliminary Results

Abstract: Background: Accurate histopathological evaluation of lymph nodes (LNs) is essential for reliable staging in prostate cancer. In routine practice, conventional techniques only examine parts of the LN. Molecular nodal staging methods are limited by their high costs and extensive time requirement. One-step nucleic acid amplification (OSNA) determines the metastatic status of the complete LN and allows for rapid intraoperative detection of LN metastases. OSNA has been proposed for diagnosis of LN metastases from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Therefore, it seems that in some cases, advanced and poorly differentiated tumors might show a lack of CK19 expression, so that metastases are not detectable by OSNA. However, in our pilot study analyzing primary PCa specimens, CK19 mRNA could be detected by OSNA in all cases, regardless of the degree of tissue differentiation [ 21 ]. Further investigations are needed to clarify this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems that in some cases, advanced and poorly differentiated tumors might show a lack of CK19 expression, so that metastases are not detectable by OSNA. However, in our pilot study analyzing primary PCa specimens, CK19 mRNA could be detected by OSNA in all cases, regardless of the degree of tissue differentiation [ 21 ]. Further investigations are needed to clarify this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies revealed that CK19 expression frequently occurs in basal as well as in luminal cells of normal, dysplastic, and benign hyperplastic prostatic tissues and in PCa [ 20 ]. Using the OSNA assay, our group recently detected a high number of CK19 mRNA copies in all PCa specimens examined [ 21 ]. This suggests that OSNA may be suitable to identify LNM and to improve LN staging in PCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially developed for intra-operative SLN evaluation in breast cancer [ 13 ], and its suitability was demonstrated in a meta-analysis of 19 studies with over 6000 LNs [ 14 ]. It can evaluate LNs within 30 min, and its feasibility in several other cancer entities, including lung, thyroid, uterus, head and neck, and prostate cancers, has been demonstrated previously [ 15 , 16 , 17 , 18 , 19 ]. Another focus was on tumors of the gastrointestinal tract, mainly on colorectal cancers [ 20 ].…”
Section: Introductionmentioning
confidence: 89%
“…Regarding urological tumours, based on previous studies that demonstrated the expression of CK19 in PCa tissue, Winter et al showed that the OSNA method can detect CK19 mRNA in 100% of primary PCa tumours regardless of Gleason score and even more effectively than CK19 IHC expression, suggesting the valid application of this technique in LN evaluation [23]. In a very recent study, Engels et al [24] demonstrated that OSNA can identify nodal metastases at an equivalent or, in cases of micrometastases, better rate than enhanced histological examination in PCa patients, con rming its promising use in intraoperative decision-making in personalized LN surgery.…”
Section: Introductionmentioning
confidence: 99%